2009
DOI: 10.1123/pes.21.4.462
|View full text |Cite
|
Sign up to set email alerts
|

Secular Trends in Youth Physical Activity and Parents’ Socioeconomic Status from 1977 to 2005

Abstract: The aim of this study was to investigate the relationship between youth physical activity and family socioeconomic status (FSES) over 28 years. As a part of the Finnish Adolescent Health and Lifestyle Survey a random sample of 12-, 15- and 18-year-old boys and girls participated in a nation-wide survey by answering questions every second year, from 1977 to 2005, on, among other things, leisure time physical activity and sport participation. Father's education represented FSES. The results showed that there wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
36
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(42 citation statements)
references
References 27 publications
4
36
0
2
Order By: Relevance
“…PA location seems to be relevant. Telama et al (2009) concluded that children of parents with higher SES had more access to physical and sportive practices over 28 years (from 1977 to 2005). Although, there was not such evidence when comparing organized PA in the school environment and comparing children`s spontaneous PA.…”
Section: Discussionmentioning
confidence: 99%
“…PA location seems to be relevant. Telama et al (2009) concluded that children of parents with higher SES had more access to physical and sportive practices over 28 years (from 1977 to 2005). Although, there was not such evidence when comparing organized PA in the school environment and comparing children`s spontaneous PA.…”
Section: Discussionmentioning
confidence: 99%
“…Participation in physical activity is unevenly distributed across population groups. Various writers have discussed [12,15,16] that associations between childhood socioeconomic position, social mobility, and physical activity and fitness may run through the mechanisms, such as improved socioeconomic circumstances leading to greater social or economic and psychological support for physical activity for example through more flexible work hours and higher income; a low social class may weaken parents' ability to transport children to organized sports, as well as to afford the fees and equipment required for the young person to participate.…”
Section: From Childhood To Adolescence and Adulthoodmentioning
confidence: 98%
“…Upward social mobility, defined as reaching a higher level of educational attainment than one's parents, was associated with a greater likelihood of high physical activity in adulthood and a greater likelihood of a high fitness level. The results of secular trends in the Finnish Adolescent Health and Lifestyle Survey from 1977 to 2005 [16] showed that participation in youth sport organized by sport clubs was strongly associated with parental socioeconomic status over a period of 28 years in both sexes. Social inequality was smaller in sport organized by schools and in young people's spontaneous physical activities.…”
Section: From Childhood To Adolescence and Adulthoodmentioning
confidence: 98%
See 1 more Smart Citation
“…It is worth mentioning the overall findings for different reasons. First, unlike studies with older children and adolescents, low SES children are less active than their higher SES peers because of the lack of access to equipment and facilities 29 ; HSES children have easier access to structured physical activities and sports paid by their parents 30 . This may not be relevant for preschoolers as their PA engagement may take place in more informal situations that do not require payment 31 .…”
Section: Discussionmentioning
confidence: 99%